COMPUTER SECURITY SYSTEM - Ristyawati Ristyawati (JAKSTIK Journal, 2006)
Computer system is a system that transforms data into information. Thus, if there are people who are not entitled to enter into the computer system, important information and valuable can be stolen or modified.